Problemi di edizione dei più antichi incantesimi tedeschi - Eleonora Cianci (Filologia Germanica)
The oldest German charms: issues on textual criticism. Medieval German charms show two sets of problems when dealing with textual criticism: on the one hand, the issue of the charm as a genre and, on the other hand, the complexity of the manuscript transmission. Each critical edition should indeed fit a proper method, which may vary according to the textual genre, the historical period, and the transmission features to get as closer as possible to the original text, even when very little is known about its existence. This paper investigates all the known German charms of the 9th and 10th century: they happen to share important features, such as a manuscript transmission based on codex unicus, the marginal position of the text on the page and in the manuscript itself, the rare paratextual elements and the relationship between Latin and German language within the text. In this period, all charms are deeply rooted in a monastic environment and were not perceived as “magic” since they were written in the same books containing other Christian texts. Indeed, all these features change again if we consider the charms of the following centuries, and then the author of a critical edition must pay attention to other problems, such as, for example, a manuscript tradition based on many variant versions of the same text and also based on increasing contamination of different motifs merging in similar texts.